3(3x+2)=-5(4x-2)+2x

Simple and best practice solution for 3(3x+2)=-5(4x-2)+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x+2)=-5(4x-2)+2x equation:


Simplifying
3(3x + 2) = -5(4x + -2) + 2x

Reorder the terms:
3(2 + 3x) = -5(4x + -2) + 2x
(2 * 3 + 3x * 3) = -5(4x + -2) + 2x
(6 + 9x) = -5(4x + -2) + 2x

Reorder the terms:
6 + 9x = -5(-2 + 4x) + 2x
6 + 9x = (-2 * -5 + 4x * -5) + 2x
6 + 9x = (10 + -20x) + 2x

Combine like terms: -20x + 2x = -18x
6 + 9x = 10 + -18x

Solving
6 + 9x = 10 + -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
6 + 9x + 18x = 10 + -18x + 18x

Combine like terms: 9x + 18x = 27x
6 + 27x = 10 + -18x + 18x

Combine like terms: -18x + 18x = 0
6 + 27x = 10 + 0
6 + 27x = 10

Add '-6' to each side of the equation.
6 + -6 + 27x = 10 + -6

Combine like terms: 6 + -6 = 0
0 + 27x = 10 + -6
27x = 10 + -6

Combine like terms: 10 + -6 = 4
27x = 4

Divide each side by '27'.
x = 0.1481481481

Simplifying
x = 0.1481481481

See similar equations:

| 15/(5/9)= | | 2x+15=9x+36 | | 3x-2=8+2x | | 12-(10x)+3x-(-10)= | | 36b^2-121g^2= | | 4r^2+12rt+9t^2= | | 8x^2-10x-25= | | 4f/58 | | 23-6=x | | 7x^2+79x+22=0 | | f(pi/6)=2sin(pi/6)-cos2(pi/6) | | 8=4xq | | 15b^2-21b-72= | | 12x^2-11x-36= | | 2*sin(pi/6) | | 4x-15+2x-10=37 | | 100a^2-196= | | (x-1)(x+5)=5 | | 2x-x^2+24=0 | | 2x^3-6x^2-56x= | | 2x^2+6x-4= | | 2x^3+5x-13=0 | | x^3+3x^2-40x= | | (2x+3)=(75-2x) | | 5y-26=-6+9y | | 3(x*x)=243 | | ln(y^2+15)=ln(y+3)+ln(y) | | -x^2-11x-30= | | x^3-3x^2-54x= | | 36b^2+23b-3= | | -x^2-14x-48= | | x^2-24x+24y-144=0 |

Equations solver categories